Odpowiedź :
d)
6 * x - 4 + 4 * x = 56
10x - 4 = 56
10x = 56 + 4
10x = 60 | : 10
x = 6
e)
2 * x - 3 + x = 9
3x - 3 = 9
3x = 9 + 3
3x = 12 | : 3
x = 4
f)
3 * x - 5 - x = 11
2x - 5 = 11
2x = 11 + 5
2x = 16 | : 2
x = 8
d)
2 * x = 12 - 2 * x
2x = 12 - 2x
4x = 12 | : 4
x = 3
e)
9 * x = 3 * x + 12
9x = 3x + 12
9x - 3x = 12
6x = 12 | : 6
x = 2
f)
10 * x = 4 * x - 6
10x = 4x - 6
10x - 4x = -6
6x = -6 | : 6
x = -1
d)
8 - 2 * x = -4 + 2 * x
8 - 2x = -4 + 2x
-2x - 2x = -4 - 8
-4x = -12 | : (-4)
x = 3
e)
9 * x - 7 = 3 * x + 5
9x - 7 = 3x + 5
9x - 3x = 5 + 7
6x = 12 | :6
x = 2
f)
3 - 10 * x = 9 - 4 * x
3 - 10x = 9 - 4x
-10x + 4x = 9 - 3
-6x = 6 | : (-6)
x = -1
d)
-3 + 7 * x - 2 = 3 * x - 11 + 6 * x
-3 + 7x - 2 = 3x - 11 + 6x
7x - 3x - 6x = -11 + 3 + 2
-2x = -6 | : (-2)
x = 3
e)
4 + 5 * x - 2 = 7 * x - 7
4 + 5x - 2 = 7x - 7
5x - 7x = -7 - 4 + 2
-2x = -9 | (-2)
x = 9/2
f)
-8 + 7 * x + 3 = 5 * x + 4 + 4 * x + 5
-8 + 7x + 3 = 5x + 4 + 4x + 5
7x - 5x - 4x = 4 + 5 + 8 - 3
-2x = 14 | : (-2)
x = -7